2022
DOI: 10.1007/s40572-022-00344-w
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Long-Term Exposure to Ambient PM2.5 in Asia-Pacific: a Systematic Review of Cohort Studies

Abstract: Purpose of Review Health effects of long-term exposure to ambient PM2.5 vary with regions, and 75% of the deaths attributable to PM2.5 were estimated in Asia-Pacific in 2017. This systematic review aims to summarize the existing evidence from cohort studies on health effects of long-term exposure to ambient PM2.5 in Asia-Pacific. Recent Findings In Asia-Pacific, 60 cohort studies were conducted in Australia, Mainland China, Hong Kong, Taiwan, and South Kor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 109 publications
(267 reference statements)
0
26
0
1
Order By: Relevance
“…ground-level monitoring) should be improved. 3 Nevertheless, it may be useful to assess emissions inventories per country, sector or source, if available (or modelled inventory data if not), to advocate for air pollution mitigation measures targeting specific sectors and sources. For example, policy-makers may refer to the Climate Trace independent greenhouse gas emissions tracking database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ground-level monitoring) should be improved. 3 Nevertheless, it may be useful to assess emissions inventories per country, sector or source, if available (or modelled inventory data if not), to advocate for air pollution mitigation measures targeting specific sectors and sources. For example, policy-makers may refer to the Climate Trace independent greenhouse gas emissions tracking database.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of cohort studies conducted in the Region and a worldwide meta-analysis support the association between long-term exposure to PM 2.5 and increased all-cause mortality. 3 , 4 While PM 2.5 concentrations are decreasing in some areas of the Western Pacific Region, 5 the increases in major sources of PM 2.,5 , such as traffic, industry, energy production and agriculture, are putting populations at higher risk from ambient compared to indoor levels of PM 2.5 . 6 Thus, assessing outdoor PM 2.5 concentrations’ impact on public health is important to protect populations.…”
Section: Introductionmentioning
confidence: 99%
“…These pollutants enter the human body through the airway and contribute to the emergence of important adverse health events (Li et al, 2022 ). A number of studies have demonstrated the extent of these adverse effects, including ischemic heart disease and several respiratory diseases (Dominski et al, 2021 , Yang et al, 2022a , 2022b ), stroke (Wu et al, 2022 ), respiratory and cardiovascular hospital admissions and cancer (Maciel et al, 2019 ; Yang et al, 2022a , 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…Acute PM2.5 exposure can trigger an inflammatory response, oxidative stress, and apoptosis in lung tissue [ 2 ]. Long-term exposure to PM2.5 may increase the incidence of cardiovascular diseases, renal disease, type 2 diabetes mellitus, and chronic obstructive pulmonary disease (COPD) [ 3 ]. PM also increases the risk of myocardial infarction, stroke, cardiac failure, coronary heart disease, pneumonia, acute respiratory distress syndrome, renal failure, hepatic injury, cerebrovascular diseases, gastrointestinal disorders, and inflammation in humans [ 4 ].…”
Section: Introductionmentioning
confidence: 99%